(untitled) (Orinoquia, 2021)
Aquatic ecosystems are susceptible to pollution, with toxic metals being compounds that have deleterious impacts on organisms. Most of the metals bioaccumulate in the food chain and therefore quantifying their concentration in the tissues of waterfowl can determine their environmental impact. Therefore, the aim of this study is to determine the concentration of mercury, lead, arsenic or cadmium in the feathers of the garza grande (Ardea alba), the corocora (Eudocimus ruber) and the ibis de cara roja (Phimosus infuscatus), species living near the Ocoa river in Villavicencio-Meta, Colombia. For this purpose, a preliminary survey will be carried out to identify key nesting sites of the corocora (Eudocimus ruber), Ibis de cara roja (Phimosus infuscatus) and the Garza grande (Ardea alba). Subsequently, six different feather collection sites will be selected, where feathers from each species will be collected and sorted (n = 3 per point) and stored in airtight bags to be taken to the laboratory, where they will be prepared for shipment to a reference laboratory, where toxic metals will be determined by atomic absorption spectrometry (AA). The results will be analysed by two-way ANOVA and Tukey’s test (p<0.05). At the end of this study we expect to determine the concentration of at least one toxic metal in the feathers of the Corocora, Ibis de cara roja and Garza grande, demonstrating their potential as reliable non-invasive biomarkers for the study of ecotoxicology in the region, raising awareness among the population of the sector about the importance of environmental conservation and the potential risk of toxic metals on animal and environmental health.